2013
DOI: 10.4161/hv.22231
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adjuvanted seasonal influenza vaccines (Inflexal V®and Fluad®) in preventing hospitalization for influenza and pneumonia in the elderly

Abstract: Annual vaccination is the main mean of preventing influenza in the elderly. In order to evaluate the effectiveness of the adjuvanted seasonal influenza vaccines available in Italy in preventing hospitalization for influenza and pneumonia, a matched case-control study was performed in elderly subjects during the 2010–2011 season in Genoa (Italy). Cases and controls were matched in a 1:1 ratio according to gender, age, socio-economic status and type of influenza vaccine. Vaccine effectiveness was calculated as I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…The oil-in-water adjuvant MF59™ contains polysorbate 80, sorbitan trioleate, trisodium citrate dehydrate, citric acid monohydrate, and has been shown to enhance immune responses to seasonal influenza vaccine compared with non-adjuvanted vaccine [10,38]. An MF59™-adjuvanted influenza vaccine (Fluad™) is licensed and widely used, and has been shown to significantly reduce hospitalization for influenza and pneumonia compared with non-adjuvanted vaccine in elderly people [39]. However, there have been no prospective, randomized clinical trials of vaccine efficacy of this formulation in people aged ≥65 years [10].…”
Section: Discussionmentioning
confidence: 99%
“…The oil-in-water adjuvant MF59™ contains polysorbate 80, sorbitan trioleate, trisodium citrate dehydrate, citric acid monohydrate, and has been shown to enhance immune responses to seasonal influenza vaccine compared with non-adjuvanted vaccine [10,38]. An MF59™-adjuvanted influenza vaccine (Fluad™) is licensed and widely used, and has been shown to significantly reduce hospitalization for influenza and pneumonia compared with non-adjuvanted vaccine in elderly people [39]. However, there have been no prospective, randomized clinical trials of vaccine efficacy of this formulation in people aged ≥65 years [10].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction was achieved despite the preferential use of aTIV in older and more frail individuals. Smaller Italian studies have confirmed the effectiveness of aTIV in elderly individuals in long‐term care, and those living in the community . A study in Canada compared the effectiveness of aTIV with TIV to prevent laboratory‐confirmed influenza in ≥65‐year‐olds, specifically selecting half the participants to be ≥85 years of age, and included those living in care or in the community .…”
Section: Adjuvanted Influenza Vaccinementioning
confidence: 99%
“…A case-control study conducted in Italy during the 2010-11 season compared patients hospitalized with influenza or pneumonia and matched non-hospitalized persons and found a non-significant VE for IIVa3 of 87.8% (0-98.9%) (34). However, these studies relied on administrative databases in which cases would not always have been laboratory-confirmed, which has been identified as a methodological shortcoming of administrative data.…”
Section: Iiva Effectiveness In Preventing Influenza and Influenza-relmentioning
confidence: 99%